2016
DOI: 10.1038/lsa.2016.120
|View full text |Cite
|
Sign up to set email alerts
|

Supra-(carbon nanodots) with a strong visible to near-infrared absorption band and efficient photothermal conversion

Abstract: A novel concept and approach to engineering carbon nanodots (CNDs) were explored to overcome the limited light absorption of CNDs in low-energy spectral regions. In this work, we constructed a novel type of supra-CND by the assembly of surface charge-confined CNDs through possible electrostatic interactions and hydrogen bonding. The resulting supra-CNDs are the first to feature a strong, well-defined absorption band in the visible to near-infrared (NIR) range and to exhibit effective NIR photothermal conversio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
147
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 262 publications
(155 citation statements)
references
References 45 publications
4
147
0
Order By: Relevance
“…A single complexes achieves multimodal imaging and multitherapy. Li et al [155,156] found that the yellow CDs from CA and urea can aggregate and form blue supra-CDs in the high humidity environment (RH > 60%). This blue supra-CDs exhibited a broad absorption peak in the NIR region which is responsible to the high photothermal conversion efficiency 52%) under 732 nm laser of 0.5 W cm −2 .…”
Section: Fluorescent Cds Conjugated With Photothermal Therapeutic (Ptmentioning
confidence: 99%
“…A single complexes achieves multimodal imaging and multitherapy. Li et al [155,156] found that the yellow CDs from CA and urea can aggregate and form blue supra-CDs in the high humidity environment (RH > 60%). This blue supra-CDs exhibited a broad absorption peak in the NIR region which is responsible to the high photothermal conversion efficiency 52%) under 732 nm laser of 0.5 W cm −2 .…”
Section: Fluorescent Cds Conjugated With Photothermal Therapeutic (Ptmentioning
confidence: 99%
“…Carbon dots (CDs) satisfy the requirements of low toxicity,11 biocompatibility,12 high photostability,13 and low cost,14 and offer versatile luminescent properties suitable for a variety of applications 15, 16, 17, 18, 19, 20, 21, 22. Phosphorescence from CDs in PVA matrix was firstly reported by Zhao's group in 2013 23.…”
mentioning
confidence: 99%
“…The Raman spectra of the CDs are shown in Figure 3c. Here, two characteristic peaks at 1335 and 1571 cm −1 correspond to the disordered D band and the graphitic G band, respectively . After the addition of NaOH, the I G /I D intensity ration was shown to increase from 0.88 to 0.99, indicating better crystallinity of the CDs .…”
Section: Resultsmentioning
confidence: 99%